Development of an Equilibrium-based Model of Gasification of Biomass by Aspen Plus. (March 2017) - Gagliano, A.; Nocera, F.; Bruno, M.; Cardillo, G.
Abstract: Agricultural and forestry residues are usually processed as wastes; otherwise, they can be recovered to produce electrical and thermal energy through processes of thermochemical conversion, such us torrefaction, pyrolysis and gasification. Currently, the gasification of residual biomass for producing neutral CO2 fuel for energy production is in development stage. In this context, this study proposes anequilibrium-based model, developed by the commercial software Aspen Plus, of a co-current gasifier fueled with agriculture residual, which allows estimating the chemical composition and theheating value of the syngas produced. The prediction of such model includes the main gaseous species, the yields of char and tar and describes the gasification process through the mass and energy balances, the water-gas shift (WGS) and the methanation reaction. The model validation was carried out through the comparison with experimental data, concerning two biomass with different moisture content and different gasification conditions, for sixteen cases compared. Overall, the comparison between the results of the simulations and the experimental data have shown a good agreement.